(3eONd ebJQM dJCcjO JbGQjQ GSJOGeI GdTQcGJ GdeUQjI h GfYcGSg Ydi EOQGc CUMGH GdeUGdM (B: s (3OQGSI ebGQfI (B/ s - (3CMeO YHOGdbGOQ TQas; (3KfGA YWjI aQGL (B: s; (3NGdO eMeO YHOGdefYe Rci dHjH (B: s ((3GdbGgQI (B: s (3CMeO YHOGdbGOQ TQa (B: s, 2015)
(3gfGc YOOB dG HCS Hg ef GdTQcGJ GdeUQjI GdJi Jbhe HGdEaUGM Yf eeGQSGJgG GdGbJUGOjI h GdHjFjI h GdGLJeGYjI ef NdGd EYOGO JbGQjQ GdGSJOGeI (B: (3EdG Cf gPG GdEaUGM jNdh ef GdJCcjO GdNGQLi deMJhGg HhGSWI WQa KGdK eDgd h eMGjO h eSJbd (B. (3h dYd Pdc eQLYg YOe hLhO eYGjjQ Ch EQTGOGJ eUQjI jecf GSJNOGegG h GdGYJeGO YdjgG NJi GdBf dJCcjO GdeMJhi GdeYdheGJi dgPG GdfhY GdLOjO fSHjB ef GdJbGQjQ (B: (3h gh GdCeQ GdPj jMO ef aYGdjI Jdc GdJbGQjQ HGdfSHI dCUMGH GdeUGdM (B: (3eeG jSJhLH eYg hLhO MGLI edMI dGbJQGM eONd dJCcjO JbGQjQ GSJOGeI GdTQcGJ GdeUQjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJLGQI (B- (3bSe GdeMGSHIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3EOQGc CUMGH GdeUGdMs; (3GdCOGA GdeSJOGes; (3JbGQjQ GdESJOGeIs